Sustainable Sugarcane Production - Singh, Priyanka; Tiwari, Ajay Kumar; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
The sugarcane crop, one of the most important crops commercially grown in about 115 countries of the world, faces a number of problems, such as low cane productivity, biotic and abiotic stresses, high cost of cultivation, postharvest losses, and low sugar recovery. This volume addresses these issues and provides a comprehensive account of the major advancements in sugarcane research. The book is compilation of recent achievements in sugarcane development and cultivation. It covers a number of improvements made in cane and sugar yield using both conventional and new biotechnological approaches by agricultural scientists and researchers. The comprehensive coverage includes sustainable sugarcane cultivation, development, and management of sugarcane production, covering farming and biotechnology, entomology, pathology, breeding, physiology, biotechnology, agronomy, seed production, and more. It also presents research on modern crop production methods in a comprehensive and easily understood manner. With chapters from expert researchers from internationally renowned institutes (primarily in India), the volume presents the latest information from the literature at the international level to make it usable to many agroecological regions of the world. It will be a valuable resource for agronomists, breeders, plant physiologists, farmers, and students of agricultural sciences.
Farming Technologies for Sugarcane Production in Upland Fields--Yang-Rui Li, Xiu-Peng Song, Jian-Ming Wu, Chang-Ning Li, Qiang Liang, Xi-Hui Liu, Wei-Zan Wang, Hong-Wei Tan, and Li-Tao Yang -- Headways in Agro-Techniques for Heightened Yield of Sugarcane: An Indian Perspectives--A. K. Singh, Menhi Lal, and Ekta Singh -- Sustainability and Efficiency of Sugarcane Cultivation in India--G. Vlontzos and P. M. Pardalos -- From Conventional to Molecular Approaches: Building Bridges for Sugarcane Genetic Improvement--Sangeeta Srivastava and Pavan Kumar -- Utilization of Sugarcane Genetic Resources for Enhanced Resilience in Diverse Conditions--Gulzar S. Sanghera, Arvind Kumar, A. Anna Durai, and K. S. Thind -- Source-Sink Dynamics in Sugarcane: Physio-Genomics Perspectives --Amaresh Chandra -- Residues Uses and Environment Sustainability--R. Rosseto, C. A. C. Crusciol, H. Cantarella, J. B. Carmo, and C. A. C. Nascimento -- Water Induced Stresses in Sugarcane: Responses and Management--R. Gomathi -- Diseases and Pests Affecting Sugarcane: Methods of Control--Yaquelin Puchades Izaguirre, Mrida Rodrguez Regal, Eida Rodrguez Lema, and Mara La O. Hechavarra -- Biological Control of Two Sugarcane Stalk Borers in the United States--Allan T. Showler -- Management of Plant-Parasitic Nematodes on Sugarcane under Tropical Conditions--A. Chaves, E. M. R. Pedrosa, L. M. P. Guimares, S. R. V. L. Maranho, and M. O. Cardoso -- Insect Vectors and Sugarcane White Leaf Disease Management--Yupa Hanboonsong -- Sugarcane Ratoon Management--S. K. Shukla, Lalan Sharma, and V. P. Jaiswal -- Mechanization for Sustainable Sugarcane Production--A. K. Singh -- Alternatives to Increase the Sustainability of Sugarcane Production in Brazil under High Intensive -- Mechanization--H. C. J. Franco, S. G. Q. Castro, G. M. Sanches, O. T. Klln, R. O. Bordonal, B. M. M. N. Borges, and C. D. Borges -- Transfer of Technology Approaches for Sustained Sugarcane Productivity--T. Rajula Shanthy.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / General; Sugarcane; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; Electronic books